Tigerheart's Shadow: Warriors Super Edition #10 - Hunter, Erin (New York, NY : Harper, an imprint of HarperCollins Publishers, 2017)
After the medicine cat has a dark vision during an already dark and uncertain period for ShadowClan, Tigerheart considers leaving the clan for good in order to save it.
"Exclusive manga adventure inside!"--Cover.
Includes manga written by Dan Jolley, art by James L. Barry.
Includes excerpt from Broken pride in the Bravelands series.
New Kids Book Winter 2023.
Keywords: Adventure and adventurers -- Fiction; Fantasy; JUVENILE FICTION -- Animals -- Cats; JUVENILE FICTION -- Fantasy & Magic; JUVENILE FICTION -- Action & Adventure -- General; Cats -- Fiction